2012
DOI: 10.1007/s11356-012-1266-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic exposure to radiofrequency electromagnetic fields on energy balance in developing rats

Abstract: The effects of radiofrequency electromagnetic fields (RF-EMF) on the control of body energy balance in developing organisms have not been studied, despite the involvement of energy status in vital physiological functions. We examined the effects of chronic RF-EMF exposure (900 MHz, 1 V m(-1)) on the main functions involved in body energy homeostasis (feeding behaviour, sleep and thermoregulatory processes). Thirteen juvenile male Wistar rats were exposed to continuous RF-EMF for 5 weeks at 24 °C of air tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 37 publications
4
16
3
1
Order By: Relevance
“…As previous study, spectral analysis confirmed that there were no effects of RF-EMF exposure on the EEG signal measured at the electrodes [4].…”
Section: Methodssupporting
confidence: 85%
See 3 more Smart Citations
“…As previous study, spectral analysis confirmed that there were no effects of RF-EMF exposure on the EEG signal measured at the electrodes [4].…”
Section: Methodssupporting
confidence: 85%
“…Our previous study showed that this intensity of exposure does not induce central heating. In this work, this intensity was associated with a significantly lower tail skin temperature (1.21°C below the control value at a T a of 31°C), independently of the sleep stage [4]. The present study aimed at assessing the changes in thermal preference and sleep stage distribution that may potentially be influenced by a difference in skin temperature [11], [16].…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Concern has been raised about the potential negative influence of RF on a developing brain [75]. Brain development in mammals is time and growth factor-dependent and extremely sensitive to external insult that might compromise future network functions.…”
Section: The Effect Of Rf Exposure In Vivo: New Insights On Biosystemmentioning
confidence: 99%